2017
DOI: 10.1093/jnci/djx238
|View full text |Cite
|
Sign up to set email alerts
|

MAX Mutations in Endometrial Cancer: Clinicopathologic Associations and Recurrent MAX p.His28Arg Functional Characterization

Abstract: These data highlight the importance of MAX mutations in EC and point to increased vascularity as one mechanism contributing to clinical aggressiveness of EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, among the top candidates an important factor with a negative β value was FOXA2, the Forkhead Box A2, an essential TF for fertility and uterine function ( 25 , 26 ). In addition, other top TFs with high β values were Max Dimerization Protein MGA, a negative regulator of MYC pathway and implicated in endometrial cancers ( 27 , 28 ), and PAX5 is involved in gene regulation in many tissues. Overall, we found that differences in TFBS numbers could explain variation in gene expression to a modest extent overall, while there are also many TFs explaining a large extent of interspecies variation for specific genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, among the top candidates an important factor with a negative β value was FOXA2, the Forkhead Box A2, an essential TF for fertility and uterine function ( 25 , 26 ). In addition, other top TFs with high β values were Max Dimerization Protein MGA, a negative regulator of MYC pathway and implicated in endometrial cancers ( 27 , 28 ), and PAX5 is involved in gene regulation in many tissues. Overall, we found that differences in TFBS numbers could explain variation in gene expression to a modest extent overall, while there are also many TFs explaining a large extent of interspecies variation for specific genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, among the top candidates an important factor with a negative β value was FOXA2, the Forkhead Box A2, an essential transcription factor for fertility and uterine function 25,26 . In addition, other top transcription factors with high β values were Max Dimerization Protein MGA, a negative regulator of MYC pathway and implicated in endometrial cancers 27,28 , PAX5 involved in gene regulation in many tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Germline MAX variants have been implicated in PPGL and renal oncocytoma and somatic variants have been identified in small cell carcinoma of the lung (Kurschner, et al 2017;Romero, et al 2014). Other tumours reported in association with MAX variants include endometrial carcinoma, ganglioneuromas, neuroblastoma, pancreatic cancer, lung adenocarcinoma and breast cancer (Seabrook, et al 2021;Walker, et al 2018). In one study, germline MAX variants accounted for approximately 1% of PPGLs in patients with a negative RET, VHL, SDHB, SDHC, SDHD, and TMEM127 genetic screen, thus making it very rare cause of PPGL (Burnichon, et al 2012).…”
Section: Introductionmentioning
confidence: 99%